The mediating role of intercultural communication apprehension in the relationship between ethnocentrism and attitude towards asylum-seekers of nursing students. (December 2022) - Kuru Alici, Nilgun; Kaya, Yunus
Abstract: Background: In order to provide culturally appropriate care, nursing students' intercultural communication anxiety, ethnocentrism and attitudes towards refugees should be examined. Objectives: This study aimed to examine the relationship among ethnocentrism and attitudes towards refugees in nursing students and to determine whether intercultural communication apprehension could mediate the relationship between ethnocentrism and attitude towards asylum-seekers. Design: A cross-sectional, descriptive design. Participants: 226 nursing students in Turkey. Methods: Data were collected using ethnocentrism, intercultural communication apprehension, and attitudes towards asylum-seekers scales and analyzed with Pearson's correlation coefficient and Baron and Kenny's three-regression analysis and Sobel test. Results: Ethnocentrism was positively associated with both intercultural communication apprehension and attitudes towards asylum-seekers scale. Intercultural communication apprehension was positively associated with attitudes towards asylum-seekers scale. Intercultural communication apprehension mediated the relationship between ethnocentrism and attitudes towards asylum-seekers (Z = 4.0497, p < 0.001). Conclusion: In line with these results, intercultural communication apprehension was a crucial mediator between ethnocentrism and attitudes towards asylum-seekers. Interventions to improve intercultural communication apprehension of nursing students should include nursing students' ethnocentrism and attitude towards refugees. Highlights: Intercultural communication apprehension (ICA) was positively associated with attitudes towards asylum-seekers (ATAS). ICA mediated the relationship between ethnocentrism (EC) and ATAS. EC was positively associated with both ICA and ATAS.